Insights into the Moisture Scavenging Properties of Different Types of Starch in Tablets Containing a Moisture-Sensitive Drug - Veronica, Natalia; Hiew, Tze Ning; Liew, Celine Valeria; Heng, Paul Wan Sia (Molecular pharmaceutics, 2020)
Starch is a commonly used excipient in the pharmaceutical industry. However, information on the effect of the moisture scavenging properties of starch to protect moisture-sensitive drugs is limited. The interaction between starch and moisture is of particular interest as moisture fugacity can impact drug stability. In this study, the moisture behavior of different starches was examined for an understanding of its role in the degradation of acetylsalicylic acid. The starches were characterized for their dimensional- and moisture-related properties. Stability testing was carried out on tablets containing acetylsalicylic acid and different starches. Although moisture sorption processes were visually comparable for the different starches, quantitative differences were found in their moisture interaction and distribution. From the sorption isotherms, moisture monolayer coverage and area of hysteresis were found to correlate well with the percentage of acetylsalicylic acid degradation. The lowest percentage of acetylsalicylic acid degradation was observed in starch that exhibited high monolayer coverage, large area of hysteresis, and good capacity for internally absorbed moisture. Findings from this study highlighted the value of moisture scavenging excipients when formulating moisture-sensitive drug products. Clearly, the assessment of moisture sorption properties of excipients during the preformulation phase can be an invaluable exercise for identifying the best possible ingredients in formulations where moisture sensitivity is an area of concern.